Synthesis and characterization of DNA fenced, self-assembled SnO2 nano-assemblies for supercapacitor applications. Issue 8 (22nd January 2016) - Nithiyanantham, U; Ramadoss, Ananthakumar; Kundu, Subrata
Abstract : Self-assembled, aggregated, chain-like SnO2 nano assemblies are synthesized at room temperature within an hour in DNA scaffold. Formation and growth mechanism are elaborated. The SnO2 nano-assemblies are utilized as potential anode material in electrochemical supercapacitor studies. Abstract : Self-assembled, aggregated, chain-like SnO2 nano-assemblies were synthesized at room temperature by a simple wet chemical route within an hour in the presence of DNA as a scaffold. The average size of the SnO2 particles and the chain diameter were controlled by tuning the DNA to Sn(ii ) molar ratio and altering the other reaction parameters. A formation and growth mechanism of the SnO2 NPs on DNA is discussed. The SnO2 chain-like assemblies were utilized as potential anode materials in an electrochemical supercapacitor. From the supercapacitor study, it was found that the SnO2 nanomaterials showed different specific capacitance ( C s ) values depending on varying chain-like morphologies and the order of C s values was: chain-like (small size) > chain-like (large size). The highest C s of 209 F g −1 at a scan rate of 5 mV s −1 was observed for SnO2 nano-assemblies having chain-like structure with a smaller size. The long term cycling stability study of a chain-like SnO2 electrode was found to be stable and retained ca. 71% of the initial specific capacitance, even after 5000 cycles. A supercapacitor study revealed that both morphologies can be used as a potential anode material and the best efficiency was observed for small sized chain-like morphology which is due to their higher BET surface area and specific structural orientation. The proposed route, by virtue of its simplicity and being environmentally benign, might become a future promising candidate for further processing, assembly, and practical application of other oxide based nanostructure materials.